2012
DOI: 10.1186/1746-6148-8-72
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prolactin receptors in normal canine mammary tissue, canine mammary adenomas and mammary adenocarcinomas

Abstract: BackgroundMammary tumors represent the most common neoplastic disease in female dogs. Recently, the promoting role of prolactin (PRL) in the development of human breast carcinoma has been shown. Possible proliferative, anti-apoptotic, migratory and angiogenic effects of PRL on human mammary cancer cells in vitro and in vivo were suggested. The effects of PRL are mediated by its receptor, and alterations in receptor expression are likely to play a role in tumor development. Currently, not much data is available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 48 publications
3
10
0
1
Order By: Relevance
“…Normal canine mammary tissues and benign lesions of the mammary gland were found to express high levels of PRL-Rs. Malignancy is controversially correlated with the expression of this receptor, which was compatible with our findings [19] . The lack of immunoreactivity for AR in most of the cases was associated with the shortfall of the selected clone of the receptor marker applied in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Normal canine mammary tissues and benign lesions of the mammary gland were found to express high levels of PRL-Rs. Malignancy is controversially correlated with the expression of this receptor, which was compatible with our findings [19] . The lack of immunoreactivity for AR in most of the cases was associated with the shortfall of the selected clone of the receptor marker applied in this study.…”
Section: Discussionsupporting
confidence: 82%
“…A study showed that bitches with mammary tumors have higher serum PRL levels than healthy ones, and PRL levels in mammary tissue are greater in MMT than in BMT or normal glands, suggesting that neoplastic mammary tissue could be a source of PRL (Queiroga et al, 2005). Moreover, Michel et al, (2012) observed that PRL receptor expression is lower in MMT than BMT, suggesting that the loss of this receptor may be a characteristic of tumor dedifferentiation.…”
Section: Hormonal Factorsmentioning
confidence: 96%
“…Recently, the occurrence of prolactin receptor was also described in normal mammary glands and in benign and malignant mammary tumours (Michel and others 2012). …”
Section: Introductionmentioning
confidence: 99%